Strategic Bank Monitoring and Firms' Debt Structure - Eirik Gaard Kristiansen (Norges Bank, 2005)
Firms choose debt structure and competing banks choose monitoring intensity. Monitoring improves credit allocation, but creates informational lock-in effects in bank-borrower relationships. In a competitive credit market, banks dissipate anticipated profit from serving locked-in borrowers subsequently revealed to the bank as good to attract new borrowers with unknown credit quality. Consequently, banks' lending strategies result in cross-subsidies from good to bad borrowers. We investigate how firms' choice of debt structure interacts with the cross-subsidies inherent in banks' lending strategies. The analysis sheds light on how dynamic bank competition determines monitoring intensity, seniority, and maturity structure in bank dependent industries.
hdl:11250/2498427
Keywords: D82; G32; G21; L14; 330; corporate debt structure; bank lending; lock-in effects